PEMBERIAN PUPUK KANDANG AYAM DENGAN MEDIUM CAMPURAN GAMBUT DAN PMK TERHADAP PERTUMBUHAN BIBIT KELAPA SAWIT (Elaeis guineensis Jacq) DI PEMBIBITAN UTAMA - Leo Rencus Sihite; Erlida Ariani (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
This study aimed to determine the effect of chicken manure and peat mixture with PMK medium and its interaction with the growth of oil palm (Elaeis guineensis Jacq.) In the main nursery, as well as to get the best combination treatment. This study was conducted over four months from the month of December 2015 to April 2016. The research was conducted dikebun trial Faculty of Agriculture, University of Riau Campus Bina Widya Km 12.5 Baru Simpang Village, District Handsome, Pekanbaru. This study uses a completely randomized design (CRD) factorial consisting of two factors, the first factor is the dose of chicken manure which consists of three levels ie P1 (chicken manure 100g/polybag), P2 (chicken manure 150 g/polybag) and P3 (chicken manure 200g/polybag). The second factor is the growing medium mixture consisting of three levels ie T1 (ratio between peat and PMK 1: 1), T2 (comparison between peat and PMK 1: 2) and T3 (comparison between peat and PMK 2: 1). Each treatment was repeated 3 times so that each experimental unit obtained 27 experimental units are 2 seed. The parameters measured were seedling height increment, the increase in diameter stump, in the number of leaves and leaf area. Based on the results of research to get the growth of oil palm seedlings tend to be good with chicken manure at a dose of 200 g/polybag and medium mixture of peat with PMK 2: 1. Keywords: Palm Oil, Chicken Manure, Peat and PMK